Analysis of definition of terms in applied linguistic empirical studies in research artices by non-native english speakers scholars in Malaysia - Chieng, Yen Yong (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aim of this study is to identify the definition of terms (DT) used in fifty research articles (RA) by non-native English speakers (NNES) scholars. The objectives of the study are: (1) identify frequency of definition of terms in each research articles (2) identify the types of definition of terms (3) identify the sections of research articles where the definition of terms appear (4) determine whether the terms are defined by referring to authoritative source or not (5) identify the linguistic features for defining terms. Selection criteria of the fifty RA is based on empirical study, English-language related studies, literature related studies or linguistic related studies and published in seven Malaysian journals written by non- native English speaker scholars. The case study is employed in studying the particular section of definition of terms. The samples of fifty RAs were collected using corpus compilation. There are four types of definition of terms identified in the study: details to show what is a term or concept (n=133, 61.0%), operational definition (n=44, 20.2%), giving components to describe what a term or concept is (n=23, 10.6%) and equivalent terms (n=21, 9.6%). Four sections in the RAs where definition of terms appeared are the Introduction section (n=156, 71.6%), Methodology section (n=22, 10.1%), Results and Discussion section (n=34, 15.6%) and Conclusion section (n=6, 2.8%). The terms are used to define by referring to both authoritative source (n=102, 46.8%) and without referring to any source (n=116, 53.2%). Linguistic features use for defining terms are details to show what a term or concept is (n=98, 58.3%), operational definition (n=33, 19.6%), giving components to describe what a term or concept is (n=21, 12.5%), and equivalent term (n=16, 9.5%). The study is useful as a reference to ESP teachers who are interested to carry out the ESP course for NNES researchers.